Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/jof5020049
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Clinical and Microbiome Risk Factors Associated with the Development of Oral Candidiasis during Cancer Chemotherapy

Abstract: Oral candidiasis is a common side effect of cancer chemotherapy. To better understand predisposing factors, we followed forty-five subjects who received 5-fluorouracil- or doxorubicin-based treatment, during one chemotherapy cycle. Subjects were evaluated at baseline, prior to the first infusion, and at three additional visits within a two-week window. We assessed the demographic, medical and oral health parameters, neutrophil surveillance, and characterized the salivary bacteriome and mycobiome communities th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 68 publications
3
51
0
4
Order By: Relevance
“…This finding supports the concept that candidiasis occurs in a polymicrobial environment enriched with these bacteria consistent with our mouse tongue infection models [13,[15][16][17]49]. We also conducted the first prospective study of oral microbiome changes in chemotherapy-treated cancer patients who develop oropharyngeal candidiasis [22]. In this cohort, development of oropharyngeal candidiasis was not associated with mycobiome structure shifts but was the result of increased Candida load, with C. albicans being the most abundant species [22].…”
Section: Evidence For Bacterial Dybiosis In Oropharyngeal Candidiasissupporting
confidence: 85%
See 2 more Smart Citations
“…This finding supports the concept that candidiasis occurs in a polymicrobial environment enriched with these bacteria consistent with our mouse tongue infection models [13,[15][16][17]49]. We also conducted the first prospective study of oral microbiome changes in chemotherapy-treated cancer patients who develop oropharyngeal candidiasis [22]. In this cohort, development of oropharyngeal candidiasis was not associated with mycobiome structure shifts but was the result of increased Candida load, with C. albicans being the most abundant species [22].…”
Section: Evidence For Bacterial Dybiosis In Oropharyngeal Candidiasissupporting
confidence: 85%
“…Oral microbiome shifts could not be explained by antibiotic intake or by a selective antibacterial action of 5-FU [41]. Interestingly, salivary fungal communities were not disturbed by chemotherapy while antibiotic use was not correlated with the risk for developing oropharyngeal candidiasis [22,41]. A chemotherapy-induced increase in oral commensal bacterial burdens, particularly aciduric bacteria such as Lactobacilli and Streptococci has also been reported in a chemotherapy treated breast cancer cohort [42].…”
Section: Immunocompomised Hosts Have Altered Oral Bacterial Microbiommentioning
confidence: 86%
See 1 more Smart Citation
“…30 There is less evidence for an association between fungi and cancer; it was shown that lesions on the oral mucosa have a greater likelihood of undergoing malignant transformation when infected with Candida compared with those that are not infected. [31][32][33] Furthermore, the adherence and biofilm production of Candida cells on patient mucosa is higher following radiotherapy, both in terms of number of cells and total biomass production, which may be associated with the increased frequency of fungal mucosal infections. 34,35 We observed candidaemia with bacteraemia in 34% of all cases consistent with the previously described data ranging from 6% to 34.5%.…”
Section: Et Al (2012) Proved That Intravenously Administered Planktonicmentioning
confidence: 99%
“…We previously found both the mouth and gut to be dominated by Candida albicans and Candida glabrata prior to mucormycosis during induction remission chemotherapy (8). Similarly, patients with a baseline microbiome community dominated by Candida and aciduric bacteria were more likely to develop oral candidiasis during antineoplastic treatment (9). Recently, variation in mycobiome composition was linked to treatment-related toxicities after autologous HSCT for multiple myeloma (10).…”
mentioning
confidence: 99%